High FGF18 expression levels predict poor prognosis in endometrial carcinoma patients and promote tumor growth and metastasis - Zheng-Yao Lei; Jian Wu; Bao-Hua Zhang; Wei Xiang; Min Wang; Bin-bin Li; Ming-Cheng Dai (Journal of International Medical Research)
Objective To investigate if fibroblast growth factor 18 (FGF18) expression plays an important role in endometrial carcinoma (EC). Methods The clinicopathological associations and prognostic value of FGF18 expression were retrospectively analyzed in 190 patients with EC. FGF18 expression was stably knocked down in EC cell lines. Changes in cell proliferation, migration, and invasion rates were examined via cell behavior experiments. Tumor growth was investigated using a xenograft mouse model. RNA sequencing (RNA-seq) was performed to identify differentially expressed genes (DEGs) in HEC-1-B cells after FGF18 knockdown, followed by pathway enrichment analysis of the DEGs. Results High FGF18 expression levels were closely correlated with EC clinicopathological features, such as histological subtype, FIGO stage, depth of myometrial invasion, and tumor size. Moreover, EC patients with high FGF18 expression levels had poorer overall survival. FGF18 knockdown in EC cells revealed its role in promoting tumor cell proliferation, migration, and invasion in vitro , as well as tumor growth in vivo . RNA-seq of HEC-1-B cells revealed that the DEGs were enriched in signaling pathways related to cell proliferation and migration. Conclusions Overexpression of FGF18 may serve as a prognostic biomarker for EC patients and is a potential therapeutic target for treating this disease.